2014
DOI: 10.4236/jmmce.2014.23029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pressure on the Mechanical Properties and Microstructure of Die Cast Aluminum A380 Alloy

Abstract: In this paper, the mechanical properties and microstructure of die cast aluminium A380 alloy casts produced under varying pressure was investigated experimentally and compared. The results obtained show better mechanical properties i.e. hardness, tensile strengths and impact strengths in the die cast A380 alloy sample that solidified at high pressure when pressure was regulated across five samples of the castings. The hardness of the die cast A380 samples that solidified under different applied pressures varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 7 publications
(16 reference statements)
0
11
0
Order By: Relevance
“…These results and conclusions are supported by previously reported studies by other investigators. 25,26 It has been shown ( Fig. 5a and b) that varying the intensification pressure during solidification has no measurable effect on either the heat transfer coefficient or the heat flux density.…”
Section: Discussionmentioning
confidence: 99%
“…These results and conclusions are supported by previously reported studies by other investigators. 25,26 It has been shown ( Fig. 5a and b) that varying the intensification pressure during solidification has no measurable effect on either the heat transfer coefficient or the heat flux density.…”
Section: Discussionmentioning
confidence: 99%
“…Increase in pressure reduces grain size and increases heat transfer rate; hence, yield strength and ductility of material increase in a squeeze casting of Al alloy [31,32]. Injection pressure die casting also improves the mechanical properties such as hardness, yield strength, tensile strength and grain refinement of A1350 [33]. Mechanical properties of cast Al-Si alloy achieved through low-pressure die casting has superior mechanical properties in comparison to sand casting, gravity die casting and high pressure die casting [34].…”
Section: Effect Of Casting Parameter On Properties Of Castmentioning
confidence: 99%
“…They have noticed that the amount of porosity does not affect the elastic characteristic (yield strength: YS) but decreases considerably the plastic properties (ultimate tensile strength: UTS and elongation: e%) of the material. With reference to the injection parameters of HDPC, Obiekea et al (2014) observed that tensile yield strength and hardness increase on the contrary of porosity when high injection pressure is applied. Such mechanical characteristics were improved due to refined microstructure obtained for the applied pressures up to 140 MPa.…”
Section: Introductionmentioning
confidence: 99%